Pemikiran Adiwarman Karim Tentang Jual Beli Online Dalam Menggunakan Akad As-Salam - Gaussian, Gini; Mirawati, Mirawati (Jurnal Hukum Ekonomi Syariah, 2022)
Salam contract is a sales contract of ordered goods between the buyer and the seller, where the specifications and prices of the ordered goods must be agreed upon at the beginning of the contract, while the payment is made upfront in full. Salam contract is a permissible sales contract based on evidence found in the Quran. The problem to be examined is Adiwarman Karim's perspective on the concept of online sales using the salam contract, its benefits, and the analysis of Islamic economics towards Adiwarman Karim's perspective on online sales using the salam contract. The objective of this research is to understand Adiwarman Karim's perspective on the concept of online sales using the salam contract, to identify its benefits, and to analyze Islamic economics towards Adiwarman Karim's perspective on online sales using the salam contract. The research method used is library research and a qualitative approach. The results of the research are as follows: 1) According to Adiwarman Karim, the salam contract has flexibility to meet the needs of society in various sectors. 2) The benefit is acquiring goods according to the buyer's needs and at the desired time. 3) In Islamic economics, the practice of buying and selling must comply with the conditions stipulated in Islamic law, namely that the contracting parties must be legally competent (baligh). Keywords: Adiwarman Karim, Online Sales, Salam Contract